Takotsubo, el gran simulador de infarto agudo de miocardio - Vega Candelario, Rodolfo; Vega Yero, Iris O.; Vega Jiménez, Junior; Hernández Casola, Tatiana (CorSalud, 2022)
Takotsubo, el gran simulador de infarto agudo de miocardio